In the zone: tax relief for the Australian bush - Fullarton, Lex; Pinto, Dale (The Tax Institute, 2019)
This article argues that the original value of the £40 per annum zone tax concession, granted in 1945 to compensate the residents of remote areas of Australia’s outback for enduring uncongenial climatic conditions, isolation and high comparative costs of living, has eroded over time. In 1945, the zone tax offset represented approximately 12% of the average weekly income. However, by 2018, though the concession had risen to $338 per annum, the concession had fallen to just 0.39% of the average income for most residents. Against this background, this article argues that the concession should be restored to its comparative value which remote taxpayers enjoyed at the time of its inception to recognise the relativity of the concession and the equity of these taxpayers compared to those who do not have to endure the uncongenial conditions that the concession was designed to compensate for.